Assessing electrodiagnostic skills among residents and fellows: Relationships between workplace‐based assessments using the Electromyography Direct Observation Tool and other measures of trainee performance. Issue 6 (13th May 2022) - Leep Hunderfund, Andrea N.; Santilli, Ashley R.; Rubin, Devon I.; Laughlin, Ruple S.; Sorenson, Eric J.; Park, Yoon S.
Abstract: Introduction/Aims: Graduate medical education programs must ensure residents and fellows acquire skills needed for independent practice. Workplace‐based observational assessments are informative but can be time‐ and resource‐intensive. In this study we sought to gather "relations‐to‐other‐variables" validity evidence for scores generated by the Electromyography Direct Observation Tool (EMG‐DOT) to inform its use as a measure of electrodiagnostic skill acquisition. Methods: Scores on multiple assessments were compiled by trainees during Clinical Neurophysiology and Electromyography rotations at a large US academic medical center. Relationships between workplace‐based EMG‐DOT scores (n = 298) and scores on a prerequisite simulated patient exercise, patient experience surveys (n = 199), end‐of‐rotation evaluations (n = 301), and an American Association of Neuromuscular & Electrodiagnostic Medicine (AANEM) self‐assessment examination were assessed using Pearson correlations. Results: Among 23 trainees, EMG‐DOT scores assigned by physician raters correlated positively with end‐of‐rotation evaluations ( r = 0.63, P = .001), but EMG‐DOT scores assigned by technician raters did not ( r = 0.10, P = .663). When physician and technician ratings were combined, higher EMG‐DOT scores correlated with better patient experience survey scores ( r = 0.42, P = .047), but not with simulated patient or AANEM self‐assessment examination scores. Discussion: End‐of‐rotation evaluations can provide valid assessments of trainee performance when completed by individuals with ample opportunities to directly observe trainees. Inclusion of observational assessments by technicians and patients provides a more comprehensive view of trainee performance. Workplace‐ and classroom‐based assessments provide complementary information about trainee performance, reflecting underlying differences in types of skills measured. Abstract : See Editorial on pages 647–649 in this issue